THE SPIRITUAL MEANING OF SULUK IN SYI’IR TANPA WATON - Siti Maslahah (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
Syi’ir Tanpa Waton, a work of KH Mohammad Nizam As-shofa, is a sufi poem. It is a cultural endeavor to response the modern problems of Muslims who easily judge others infidels without realizing their own infidelity. This poem is used as a closing recitation of Reboan Agung (Islamic regular study forum of Muslim conducted in every Wednesday night learning the book of Jamī’ al-uṣul fi al-uliyā’ the work of Shaykh Ahmad Dhiya 'uddin Musthofa Al-Kamisykhonawi) and the book of Al-Fatḥurrabbani wa al-Faiḍurrahmani the work of Shaykh Abdul Qadir al-Jilani. The forum took place at Islamic boarding school of Ahlus-Shofa Wal Wafa Sidoarjo, East Java. This research is inspired by spiritual emptiness caused by the modernization and the shallow understanding of Islamic teachings. Islam is studied and practiced at the level of shari'a without deepening it into higher stages of Sufism i.e. tariqa, haqiqa and even marifa. This study employs content analysis and qualitative approach aims at analyzing the message or moral values contained in the literature. Then, I classifies basic thoughts into some themes and selects these themes to find the central idea of the text. Substantively, the verses were structurely written ranging from understanding comprehensively the teachings of Islam, teachings self-awareness, the teachings of social piety (humanism) and the teachings of Sufism namely suluk practice. Suluk in Syi’ir Tanpa Waton is devided into two parts, namely: small suluk (khalwat fi al-khalwat) and big suluk (khalwat fi al-jalwat). Meanwhile, suluk nafs/soul purification and suluk Qalb/heart purification are called takhalli/purgativa. In addition to that, sirr emptying (tahalli/contemplative) followed by soul enlightening (Tajalli/Illuminativa) is a chain of process or stages that should be passed in the form of small and big suluk which take place in suluk Qalb (takhalli/purgativa) and sirr emptying (tahalli/contemplative). Suluk in the present context is urgently needed for peaceful soul to face negative effects of modernization and spiritual crisis of modern human by doing seclusion physically and mentally (qalb/jasad) from the crowd of human life. Seclusion is a symbol of taqarrub ilallāh by self-equipping with spiritual values to depend on nothing but Allah. This process will consruct oneself to be calm, patient, active, productive, firmly independent, consistent, having integrity and good personality